2007
DOI: 10.1021/bi6025374
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon Amyloid-like Fibril Morphology Is Selected via Morphology-Dependent Growth Inhibition

Abstract: The 29-residue peptide hormone glucagon readily fibrillates at low pH, but the structure and morphology of the fibrils are very sensitive to the environmental conditions. Here we have investigated the mechanism behind the differences in morphology observed when glucagon fibrils are formed at different peptide concentrations. Electron microscopy shows that fibrils formed at low glucagon concentration (0.25 mg/mL) are twisted, while fibrils formed at high concentration (8 mg/mL) are straight. Monitoring the fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
107
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(113 citation statements)
references
References 43 publications
6
107
0
Order By: Relevance
“…For FAS1-4 A546T, polymorphism is induced by differences in protein concentration. Fibrillation of the peptide hormone glucagon at different peptide concentrations also induces fibril polymorphism (67). This polymorphism arises from a concentration-dependent equilibrium between the monomeric form and a trimer.…”
Section: Discussionmentioning
confidence: 99%
“…For FAS1-4 A546T, polymorphism is induced by differences in protein concentration. Fibrillation of the peptide hormone glucagon at different peptide concentrations also induces fibril polymorphism (67). This polymorphism arises from a concentration-dependent equilibrium between the monomeric form and a trimer.…”
Section: Discussionmentioning
confidence: 99%
“…We therefore sought to investigate this process and to elucidate the molecular factors governing its occurrence and specificity. Previous studies by Andersen et al 20,56 and others [59][60][61] demonstrated that parts of fibril surfaces have the capacity to nucleate fibrillization resulting in the branching, growth away or along the parent fibril. Under conditions that favored the formation of other fibril varieties (e.g., type-4 and type-5), no secondary-nucleation events were observed, even after the addition of fresh Aβ42-M (Fig.…”
Section: Secondary Nucleation Is Fibril-type Specificmentioning
confidence: 98%
“…9,10 Previous studies involving in situ atomic force microscopy (AFM) or transmission electron microscopy (TEM) have revealed Aβ42 fibrillogenesis to proceed via the formation of highmolecular-weight protofibrils. 11,12 The kinetics of protofibril formation and stability and the structure of the final fibrils depend greatly upon ambient conditions such as pH, temperature, buffer composition, and peptide concentration, [13][14][15][16][17][18][19][20] as well as upon the hydrophobicity or hydrophilicity of the substrate. 21 Although the mechanism underlying the aggregation of Aβ peptides in vitro has been the subject of numerous investigations over the past two decades, many fundamental questions remain unanswered.…”
Section: Introductionmentioning
confidence: 99%
“…Fibril formation is accompanied by changes in secondary structure. The native state of amyloidogenic precursor proteins can be highly diverse, ranging from purely a-helical (myoglobin [114]), mixtures of a-helices and b-sheets (insulin [115] and lysozyme [116]), a/b-mixed structures (HypF N-terminal domain [117]), b-barrels (Ig light chain [118]) or natively unfolded (a-synuclein [119] and glucagon [120]). Upon fibril formation, some proteins undergo first a decrease in ordered secondary structure and a concomitant increase in random coil structures, followed by a gain in b-sheet-rich features, which make up the backbone of amyloid fibrils.…”
Section: Circular Dichroismmentioning
confidence: 99%